CELAH PALATUM (PALATOSCIZIS) - Zainul Cholid (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2013)
Cleft palate is a congenital deformity that causes a multitude of problems and represents a special challenge to the medical community. Speech production, feeding, maxillofacial growth, and dentition are just a few important developmental stages that may be affected. Beside that, these children and their families often experience serious psychological problems. A broad spectrum of variations in clinical presentation exists. Several subtypes of cleft palate can be diagnosed based on severity. The correct diagnosis of a cleft anomaly is fundamental for treatment, for further genetic and etiopathological studies, and for preventive measures correctly targeting the category of preventable orofacial clefts. These article reviews the embriology, etiology, pathophysiology, and classification of the cleft palate